Arabidopsis flippase ALA3 is required for adjustment of early subcellular trafficking in plant response to osmotic stress - Pukyšová, Vendula; Sans Sánchez, Adrià; Rudolf, Jiří; Nodzyński, Tomasz; Zwiewka, Marta (Journal of experimental botany, 2023)
To compensate for their sessile lifestyle, plants developed several responses to exogenous changes. One of the previously investigated and not yet fully understood adaptations occurs at the level of early subcellular trafficking, which needs to be rapidly adjusted to maintain cellular homeostasis and membrane integrity under osmotic stress conditions. To form a vesicle, the membrane needs to be deformed, which is ensured by multiple factors, including the activity of specific membrane proteins, such as flippases from the family of P4-ATPases. The membrane pumps actively translocate phospholipids from the exoplasmic/luminal to the cytoplasmic membrane leaflet to generate curvature, which might be coupled with recruitment of proteins involved in vesicle formation at specific sites of the donor membrane. We show that lack of the AMINOPHOSPHOLIPID ATPASE3 (ALA3) flippase activity caused defects at the plasma membrane and trans-Golgi network, resulting in altered endocytosis and secretion, processes relying on vesicle formation and movement. The mentioned cellular defects were translated into decreased intracellular trafficking flexibility failing to adjust the root growth on osmotic stress-eliciting media. In conclusion, we show that ALA3 cooperates with ARF-GEF BIG5/BEN1 and ARF1A1C/BEX1 in a similar regulatory pathway to vesicle formation, and together they are important for plant adaptation to osmotic stress.
Keywords: proteiny huseníčku; ARF; osmotic stress; Arabidopsis thaliana; Arabidopsis; Osmotic Pressure; membránové proteiny; Membrane Proteins; Arabidopsis Proteins; flippase; osmotický tlak; Cell Membrane; biologický transport; secretion; GEF; protein trafficking; buněčná membrána; endocytosis; Biological Transport